Mantra as Local Wisdom in the Ritual of Bonokeling Community, Pekuncen Village, Jatilawang District, Banyumas Regency - Suhardi, Imam; Huda, Ulul (Jurnal Lingua Idea, 2023)
Local wisdom is a collective culture that is spread and passed down traditionally in oral language. In this context, a mantra is a type of folk poetry found in almost various cultures in the Archipelago. The use of mantras in culture is inseparable from its role in a particular society. One of the communities that are still consistent in preserving the wisdom of mantras is the indigenous people of Bonokeling, who live in Pekuncen Village, Jatilawang District, Banyumas Regency. The Bonokeling indigenous people often use mantras in their various rituals. The mantra recited by the Bonokeling indigenous people has a hidden meaning. The strings of the mantra reflect the spirituality that surrounds it so that the intent and purpose of its use can be revealed.